Peran Ragam Hias Tradisional Melayu Riau pada Desain Produk Kerajinan Kayu di Pekanbaru - Bambang Sungkowo (Journal of Visual Art and Design, 2008)
Melayu Riau uses many wooden craft products, ranging from casings for rituals to varieties of souvenirs. As similar to other areas of Indonesia, Melayu Riau community possesses various decorative styles that are rich in motifs and laden with meanings. It is an endless potential source for wooden craftsmen, yet not many have optimally exploited them. This study observes wooden crafts of Melayu Riau in Pekanbaru (especially souvenirs), in order to expose the roles of traditional decorative styles of Melayu, their ridden symbolic meanings, and the possibility of using them as sources for creating various wooden craft products. To address the purpose, the study applied descriptive approach using interviews, document study, and observation as means of data collecting. Results of analysis showed that newly created wooden products from the Center of Melayu Riau Souvenirs support varieties of functions yet their aesthetic qualities are not representatively qualified. Too many products repeatedly use floral and nail kaluk motifs, as if there are no other available motifs. Thus, the products look monotonous in shapes, colors, and applied decorative elements. To make the products representatively qualified, it is better to address the aesthetic qualities of the product by exploiting varieties of motifs, alternate colors, shapes, and decorative elements.